Mattering and making ethics: On craft, embodiment and vulnerable materialities. Issue 1 (1st March 2020) - Gilmour, Ruth Elvira
AbstractUnearthing the development of my craft practice and my physicality, this critical self-portrait exposes my embodied experiences, material processes and the humanistic and scientific research entangled within my artistic investigations. By examining linkages between body, material and language, my practice concerns itself with vulnerability and the interrelations of the self and other. Initially using porcelain to explore ecocritical matters, the responsive material soon revealed potential for personal and physiological abstraction; exposing this journey, I later develop correlations with silk. Throughout this article I explain how close material relationships open space for the training and moulding of my body, ethically and for reasons of recovery and resistance.